2016
DOI: 10.1038/srep20558
|View full text |Cite
|
Sign up to set email alerts
|

The exploration of network motifs as potential drug targets from post-translational regulatory networks

Abstract: Phosphorylation and proteolysis are among the most common post-translational modifications (PTMs), and play critical roles in various biological processes. More recent discoveries imply that the crosstalks between these two PTMs are involved in many diseases. In this work, we construct a post-translational regulatory network (PTRN) consists of phosphorylation and proteolysis processes, which enables us to investigate the regulatory interplays between these two PTMs. With the PTRN, we identify some functional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Although large-scale proteomic studies have identified thousands of PTMs in protein domains, the functional significance of many of these PTMs are largely unknown, though analysis of PTMs in the context of conserved and variable residues in MSAs have provided new insights into speciation and functional specialization in signaling proteins 20, 21 . More recently, PTMs have emerged as a valuable source of information for identifying mutations associated with complex disease signaling 22-24 and identifying novel drug targets 25 . For example, cancer mutations can rewire signaling pathways by removing conserved phosphorylation sites or by introducing new phosphorylation sites 24, 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although large-scale proteomic studies have identified thousands of PTMs in protein domains, the functional significance of many of these PTMs are largely unknown, though analysis of PTMs in the context of conserved and variable residues in MSAs have provided new insights into speciation and functional specialization in signaling proteins 20, 21 . More recently, PTMs have emerged as a valuable source of information for identifying mutations associated with complex disease signaling 22-24 and identifying novel drug targets 25 . For example, cancer mutations can rewire signaling pathways by removing conserved phosphorylation sites or by introducing new phosphorylation sites 24, 26 .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 More recently, PTMs have emerged as a valuable source of information for identifying mutations associated with complex disease signaling [22][23][24] and identifying novel drug targets. 25 For example, cancer mutations can rewire signaling pathways by removing conserved phosphorylation sites or by introducing new phosphorylation sites. 24,26 To systematically identify and characterize such mutations, however, signaling and cancer variants need to be integrated and analyzed in the context of PTMs and evolutionary patterns.…”
mentioning
confidence: 99%
“…Xiao-Dong Zhang et al [23] hypothesized that drugs that target the same functional network motif could be combined to improve the therapeutic efficacy. They extracted drug combinations from the Drug Combination Database [25].…”
Section: Systems Biology Based Methodsmentioning
confidence: 99%
“…However, drug combination prediction results could be improved by reconstructing drug targets. Although computational models have been proposed from multiple aspects for predicting drug targets [27,28], these methods all consider drug-target prediction and drug combination discovery as two separate learning tasks in different computational models. Thus, we integrated drug-target prediction [29,30] and drug combination prediction [15] into a unified framework, namely the DSML algorithm, which can accurately and effectively predict drug synergy.…”
Section: Introductionmentioning
confidence: 99%